Crimes of States/Crimes of Hate: Lessons from Rwanda - Alvarez, Jose E. (1999)
This Article critiques international lawyers' assumptions about how best to pursue criminal accountability for perpetrators of atrocities such as those committed in Rwanda during 1994. It contrasts an internationalist paradigm for dealing with such atrocities, characterized by international law's state-centric orientation, with the more grass-roots perspective seen in many journalistic accounts which characterizes the underlying offenses as prototypical crimes premised on hatred of the other. The author uses the dichotomy between these two perspectives to illustrate the fallacies perpetrated by the international community's principal response to the Rwandan genocide: namely, the establishment of an international war crimes tribunal for Rwanda based in a foreign country, with foreign judges on its bench, and charged solely with the application of international norms. The author argues that the International Tribunal for Rwanda is fundamentally misconceived and may undermine the rationales for its creation to the extent that it relies on jurisdictional primacy over domestic courts, ethnic neutrality, and an emphasis on prosecuting primarily high-level perpetrators.T he author also draws larger lessons from the Rwandan example, contending that it is important to be more attentive to the characteristics of particular instances of mass atrocities and that it is wrong to adopt a one size fits all approach to international criminal adjudication. The author contends that international forms of accountability, including the proposed international criminal court, need to truly complement, and resonate with, local efforts for accountability where these are likely or can be made available